Reduction of Free Fatty Acids in Palm Kernel Oil Using Bagasse Adsorbent of Varying Masses - Caleb MacCarthy; Stephen Adusei (IPTEK The Journal for Technology and Science, 2021)
Palm kernel is an important oilseed found in the fruit of the oil palm plant. The kernel serves as the source of palm kernel oil rich in vitamin K and has zero transfat and zero cholesterol. The quality of crude palm kernel oil is dependent on the content of free fatty acids, moisture, heavy metals, oxidized products, and minor constituents such as phosphatide. The free fatty acid content, amongst other parameters, is considered a major determinant of the quality of palm kernel oil as higher contents can be detrimental to the flavor, color, stability, and safety of the oil. Hence, this present study aimed at exploring the possibility of using bagasse adsorbent (sugarcane residue) of varying masses of 1.0 g, 1.5 g, 2.0 g, and 2.5 g to reduce the free fatty acids in crude palm kernel oil. A standard test by AOCS was employed in determining the free fatty acids (%FFA) content in both the crude and bagasse treated palm kernel oil. The result of the use of bagasse adsorbent as free fatty acids reducing agent proved to be effective by reducing the FFA content of the crude palm kernel oil by 74%, 77%, 79%, and 82% for 1.0 g, 1.5 g, 2.0 g, and 2.5 g of bagasse adsorbent respectively. Therefore, the findings of this study advocate the use of bagasse adsorbent in reducing higher levels of FFA in crude palm kernel oil to its acceptable limit.